Make it out alive - Brennan, Allison (Brennan, Allison. Quinn & Costa thriller, 2026)
"Three newlywed couples have disappeared from an exclusive resort in Florida, only to turn up dead soon after. With the location and the similarities between the female victims as their only leads, it's up to the FBI Mobile Response Team to catch a serial killer before anyone else ends up dead. And they have the perfect bait--Detective Kara Quinn, who bears an uncanny resemblance to the targeted women. Undercover as newlyweds pretending to enjoy their honeymoon, Kara and FBI Agent Matt Costa set a flawless trap. When their plan works and they arrest the predator, Matt sends the rest of the team home so he and Kara can have the weekend for some much-needed R&R. But on Monday morning, the couple doesn't show up to work, and the MRT learns they never checked out of their hotel. As their team tries to find them, Matt and Kara learn the truth--the killer wasn't acting alone. He had a partner who succeeded where he failed. Kidnapped and forced into a twisted escape room, they need to find a way out, because if they don't escape, they'll die"--